Paper laminate
Patent Information
- Application Number
- JP2021121735
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-07-26
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-07-26
AI Technical Summary
【0009】 本発明によれば、耐衝撃性および加工性に優れた紙積層体を提供できる。
Smart Images

Figure 0007632152000001 
Figure 0007632152000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a paper laminate. [Background technology]
[0002] Packaging using a heat seal method is widely used for packaging general industrial products, as well as for packaging food, medicine, medical equipment, etc. For example, Patent Document 1 describes a packaging material that is made of a laminate including at least a film substrate and a sealant, in which the parallel transmitted light at a specific wavelength of the laminate is equal to or less than a specific value, and a transparent gas barrier layer is provided in the laminate.
[0003] In recent years, the problem of plastic waste has become more serious. Of the total amount of plastic produced in the world, a large amount is produced in the packaging container sector, which is the cause of plastic waste. Plastic does not decompose for a long time, and the waste turns into microplastics in the natural environment, causing serious adverse effects on the ecosystem. As a countermeasure, it has been proposed to replace plastic with paper.
[0004] For example, Patent Document 2 describes a wrapping paper that includes a paper base material, a coating layer coated on one side of the paper base material, and a thermally adhesive resin layer disposed on the other side of the paper base material via an adhesive layer, in which the coating layer has gas barrier properties and the adhesive layer is formed from a gas barrier adhesive. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-132263 A [Patent Document 2] JP 2020-196529 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, the wrapping paper described in Patent Document 2 does not consider impact resistance and processability, and there is a need for the development of wrapping paper having excellent impact resistance and processability.
[0007] Therefore, an object of the present invention is to provide a paper laminate having excellent impact resistance and processability. [Means for solving the problem]
[0008] The object of the present invention can be achieved by the following configuration. <1> A paper laminate having a barrier film layer, a paper base layer, and a heat seal layer laminated in this order, in which the tensile energy absorption in the longitudinal direction measured in accordance with JIS P 8113:2006 is X1, the tensile energy absorption in the transverse direction is Y1, the specific tensile energy absorption in the longitudinal direction measured in accordance with JIS P 8113:2006 is X2, and the specific tensile energy absorption in the transverse direction is Y2, the geometric mean of X1 and Y1 is 120 J / m 2 or more, and the geometric mean of X2 and Y2 is 1.8 J / g or more. <2> The paper base has a basis weight of 50 g / m 2 More than 120g / m 2 Below is the <1> The paper laminate described in claim 1. <3> The ratio of the basis weight of the paper base material to the basis weight of the paper laminate is 0.5 or more; <1> or <2> The paper laminate described in claim 1. <4> Vertical and horizontal measurements according to JIS P 8116:2000 beside The geometric mean of the tear strength in the direction is 1000 mN or more. <1> ~ <3> 13. A paper laminate according to any one of the preceding claims. <5> Oxygen permeability measured at 23℃ and 50% RH is 10mL / m 2 ·atm·day or less, <1> ~ <4> 13. A paper laminate according to any one of the preceding claims. <6> Water vapor permeability measured at 40℃ and 90% RH is 50g / m 2 ·day or less, <1> ~ <5> 13. A paper laminate according to any one of the preceding claims. <7> The paper laminate has a basis weight of 80 g / m2 More than 200g / m 2 Below is the <1> ~ <6> 13. A paper laminate according to any one of the preceding claims. <8> The thickness of the barrier film layer is 5 μm or more and 30 μm or less. <1> ~ <7> 13. A paper laminate according to any one of the preceding claims. <9> the barrier film layer has, from the paper substrate layer side, a substrate film, a deposition layer, and an overcoat layer in this order; <1> ~ <8> 13. A paper laminate according to any one of the preceding claims. <10> The thickness of the heat seal layer is 70 μm or less. <1> ~ <9> 13. A paper laminate according to any one of the preceding claims. <11> The heat seal layer contains at least one selected from the group consisting of polyolefin resins and water-dispersible resin binders. <1> ~ <10> 13. A paper laminate according to any one of the preceding claims. <12> <1> ~ <11> A packaging bag made using the paper laminate described in any one of the above. Effect of the Invention
[0009] According to the present invention, a paper laminate having excellent impact resistance and processability can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] A preferred embodiment of the present invention will be described below. In this specification, the range "X to Y" means "X or more and Y or less". In this specification, unless otherwise specified, operations and measurements of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity of 40 to 50%. In addition, "(meth)acrylic" is a generic term including both acrylic and methacrylic.
[0011] [Paper laminate] The paper laminate according to this embodiment (hereinafter also simply referred to as the paper laminate) is a paper laminate formed by laminating a barrier film layer, a paper base layer, and a heat seal layer in this order, and when the tensile energy absorption amount in the longitudinal direction measured in accordance with JIS P 8113:2006 is X1, the tensile energy absorption amount in the transverse direction is Y1, the specific tensile energy absorption amount in the longitudinal direction measured in accordance with JIS P 8113:2006 is X2, and the specific tensile energy absorption amount in the transverse direction is Y2, the geometric mean of X1 and Y1 is 120 J / m 2 The geometric mean of X1 and Y1 is 120 J / m or more, and the geometric mean of X2 and Y2 is 1.8 J / g or more. 2 When the geometric mean of X2 and Y2 is 1.8 J / g or more, the impact resistance and processability are excellent.
[0012] <Paper base material> (Raw pulp) The paper base material (hereinafter also simply referred to as the paper base material) constituting the paper base material layer used in the paper laminate according to this embodiment is preferably made of raw material pulp mainly composed of softwood pulp. "Raw material pulp mainly composed of softwood pulp" refers to raw material pulp in which the softwood pulp content is more than 50% by mass, and the softwood pulp content is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass. Softwood pulp has a long average fiber length, and paper base materials using softwood pulp as raw material pulp tend to have excellent impact resistance and processability.
[0013] From the viewpoint of obtaining a paper laminate having excellent impact resistance and processability, the coniferous pulp is preferably pulp obtained from one or more species selected from the group consisting of Douglas fir and pine, and more preferably pulp obtained from Douglas fir.
[0014] The raw material pulp constituting the paper base material is preferably one or more types selected from the group consisting of bleached kraft pulp and unbleached kraft pulp, and more preferably unbleached kraft pulp.
[0015] (Kappa number) From the viewpoint of obtaining a paper laminate having excellent impact resistance and processability, the kappa number of the pulp constituting the paper base material, measured in accordance with JIS P 8211:2011, is preferably 30 or more, and preferably 60 or less, more preferably 55 or less, and even more preferably 50 or less. The kappa number of the pulp constituting the paper base material is measured in accordance with JIS P 8211:2011 using a paper base pulp disintegrated in accordance with JIS P 8220-1:2012 as a sample.
[0016] (Tensile Energy Absorption (TEA)) In terms of obtaining a paper laminate having excellent impact resistance and processability, the paper base material is preferably such that, when the tensile energy absorption amount in the machine direction measured in accordance with JIS P 8113:2006 is x1 and the tensile energy absorption amount in the cross direction is y1, the geometric mean of x1 and y1 (the square root of the product of x1 and y1) is 150 J / m 2 More than 200 J / m 2 More preferably, 230 J / m 2 More preferably, 250 J / m 2 From the viewpoint of processability, it is preferably 800 J / m 2 Less than or equal to 700 J / m 2 Less than 600 J / m, more preferably 600 J / m 2 Less than 530 J / m 2 Less than or equal to 460 J / m 2 or less, and even more preferably 420 J / m or less 2 When a paper substrate having TEA properties within the above range is used, a paper laminate having the TEA properties of this embodiment can be obtained. The paper substrate has a ratio of X1 to Y1 (X1 / Y1) of preferably 0.4 or more, more preferably 0.5 or more, and preferably 2.0 or less, more preferably 1.8 or less.
[0017] (Tensile Energy Absorption Index (TEAI)) When the specific tensile energy absorption in the machine direction is x2 and the specific tensile energy absorption in the cross direction is y2, the geometric mean of x2 and y2 is preferably 1.9 J / g or more, more preferably 2.5 J / g or more, and even more preferably 3.0 J / g or more, from the viewpoint of obtaining a paper laminate having excellent impact resistance and processability, and the upper limit is not particularly limited, but is preferably 8.0 J / g or less, more preferably 7.0 J / g or less. When a paper base material having TEAI properties within the above range is used, a paper laminate having the TEAI properties of this embodiment can be obtained.
[0018] (Basic weight) The basis weight of the paper base material is preferably 50 g / m from the viewpoint of obtaining a paper laminate having excellent impact resistance and processability. 2 More preferably, 60 g / m 2 More preferably, 70 g / m 2 and preferably 120 g / m 2 Less than 110 g / m 2 Less than 105 g / m, more preferably 105 g / m 2 The basis weight of the paper base material is measured in accordance with JIS P 8124:2011. From the viewpoint of recyclability, the ratio of the basis weight of the paper base material to the basis weight of the paper laminate described below is preferably 0.5 or more, and although there is no particular upper limit, it is preferably 0.9 or less.
[0019] (Thickness) From the viewpoint of impact resistance and processability of the paper laminate, the thickness of the paper substrate is preferably 20 μm or more, more preferably 30 μm or more, even more preferably 60 μm or more, even more preferably 80 μm or more, even more preferably 100 μm or more, and preferably 200 μm or less, more preferably 170 μm or less, even more preferably 150 μm or less, and even more preferably 140 μm or less. The thickness of the paper substrate is measured in accordance with JIS P 8118:2014.
[0020] (density) The density of the paper base material is preferably 0.3 g / cm from the viewpoint of moldability. 3 More preferably, 0.5 g / cm 3 and preferably 1.2 g / cm 3 Less than 1.0 g / cm, more preferably 1.0 g / cm 3 The density of the paper substrate is calculated from the basis weight and thickness of the paper substrate obtained by the above-mentioned measuring method.
[0021] (Tear strength) From the viewpoint of impact resistance, the paper base material preferably has a geometric mean of longitudinal and transverse tear strengths measured in accordance with JIS P 8116:2000 of 1000 mN or more, more preferably 1100 mN or more, and preferably 1700 mN or less, more preferably 1600 mN or less.
[0022] (optional ingredient) The paper base material may contain optional components as necessary, such as anionic, cationic or amphoteric retention agents, drainage improvers, dry strength agents, wet strength agents, sizing agents, internal additives such as fillers, water-resistant agents, dyes, and fluorescent whitening agents. Examples of the dry strength agent include cationic starch, polyacrylamide, carboxymethyl cellulose, etc. The content of the dry strength agent is not particularly limited, but is preferably 3.0% by mass or less based on the raw pulp (bone dry mass). Examples of the wet strength agent include polyamide polyamine epichlorohydrin, urea formaldehyde resin, and melamine formaldehyde resin. Examples of the sizing agent include internal sizing agents such as rosin sizing agents, synthetic sizing agents, and petroleum resin-based sizing agents, and surface sizing agents such as styrene / acrylic acid copolymers and styrene / methacrylic acid copolymers. The content of the sizing agent is not particularly limited, but is preferably 3.0% by mass or less based on the raw pulp (bone dry mass). Examples of the fixing agent include aluminum sulfate, polyethyleneimine, etc. The content of the fixing agent is not particularly limited, but is preferably 3.0% by mass or less based on the raw pulp (bone dry mass). Examples of the filler include inorganic fillers such as talc, kaolin, calcined kaolin, calcium carbonate, calcium sulfate, barium sulfate, titanium dioxide, zinc oxide, alumina, magnesium carbonate, magnesium oxide, silica, white carbon, bentonite, zeolite, sericite, and smectite, and organic fillers such as acrylic resins and vinylidene chloride resins.
[0023] As the paper base material, for example, Clupak paper which has been subjected to Clupak treatment to shrink the paper web can be used.
[0024] <Barrier film layer> The paper laminate according to this embodiment has at least one barrier film layer on one side of the paper substrate, so as to have a barrier film layer, a paper substrate layer, and a heat seal layer in this order. The barrier film layer preferably has, from the paper substrate layer side, a substrate film, a vapor deposition layer, and an overcoat layer in this order.
[0025] (Thickness) The thickness of the barrier film layer is preferably 5 μm or more, more preferably 8 μm or more, even more preferably 10 μm or more, and is preferably 30 μm or less, more preferably 25 μm or less, even more preferably 20 μm or less. The thickness of the barrier film layer is measured in accordance with JIS P 8118:2014.
[0026] (Base film) Examples of the substrate film include resin films formed by stretching polymers such as polyethylene, polypropylene, polyester, polystyrene, acrylic resin, polycarbonate, polyurethane, polyvinyl chloride, polysulfone, polyamide, polyimide, and polyamideimide as necessary to form a film. These polymers may be used alone or in combination of two or more. Among these, the polymer constituting the substrate film is preferably one or more selected from the group consisting of polyester and polyamide, and more preferably one or more selected from the group consisting of polyethylene terephthalate (PET) and nylon. Examples of nylon include nylon 6, nylon 11, nylon 12, and nylon 66, with nylon 6 being preferred.
[0027] The thickness of the substrate film is not particularly limited, but is, for example, preferably 1 μm or more, more preferably 5 μm or more, and preferably 300 μm or less, more preferably 150 μm or less, even more preferably 50 μm or less, and even more preferably 25 μm or less.
[0028] (deposited layer) The vapor deposition layer is at least one of a layer made of metal and a layer made of ceramic. That is, the vapor deposition layer may be any of a layer made of metal, a layer made of ceramic, and a laminate of a metal layer and a ceramic layer. When the vapor deposition layer is a laminate of a metal layer and a ceramic layer, the metal layer may be on the substrate film side, or the ceramic layer may be on the substrate film side, and is not particularly limited.
[0029] The vapor-deposited layer may be any of a layer made of a metal, a layer made of a ceramic, and a laminate of these, but a layer made of a ceramic is preferred. When the vapor-deposited layer is a layer made of a metal, specific examples of the metal include aluminum, magnesium, silicon, titanium, zinc, etc. These may be used alone or in combination of two or more. Among these, aluminum is preferred. When the deposition layer is a layer made of ceramic, specific examples of the ceramic include silicon oxide, titanium oxide, aluminum oxide, magnesium oxide, zinc oxide, etc. These may be used alone or in combination of two or more. Among these, it is preferable to use one or more selected from the group consisting of silicon oxide, aluminum oxide, and magnesium oxide, more preferable to use one or more selected from the group consisting of aluminum oxide and silicon oxide, and even more preferable to use one or more selected from the group consisting of aluminum oxide and silica alumina.
[0030] The thickness of the vapor deposition layer is not particularly limited, but from the viewpoint of gas barrier properties, it is preferably 5 nm or more, more preferably 7 nm or more, and from the viewpoint of ease of handling, it is preferably 500 nm or less, more preferably 200 nm or less, even more preferably 100 nm or less, still more preferably 70 nm or less, and even more preferably 50 nm or less.
[0031] The method for forming the deposition layer on the substrate film is not particularly limited, and examples of the method include known methods such as direct vacuum deposition of the metal or ceramic constituting the deposition layer, sputtering, ion plating, etc. Among these, the vacuum deposition method is preferred.
[0032] (Overcoat layer) The overcoat layer is a layer for protecting the deposition layer. The overcoat layer is not particularly limited and may contain an organic compound, an inorganic compound, or both. That is, the overcoat layer may be any of an organic layer, an inorganic layer, and an organic-inorganic hybrid layer. Examples of the organic compound include vinyl alcohol resins such as polyvinyl alcohol, polyurethane resins, (meth)acryloyl compounds, and / or reaction products thereof. Examples of the inorganic compound include oxides of silicon, aluminum, and the like. The overcoat layer is preferably a layer containing, for example, polyvinyl alcohol and silicon oxide, (meth)acryloyl compounds, and / or reaction products thereof.
[0033] When the overcoat layer is a layer containing a (meth)acryloyl compound and / or a reaction product thereof, it may have, for example, the following embodiment, but is not particularly limited thereto. Examples of the (meth)acryloyl compound include a compound obtained by cross-linking copolymerization of a compound having a (meth)acryloyl group but not a silane coupling agent and a (meth)acryloyl group-containing silane coupling agent. The (meth)acryloyl compound preferably has two or more (meth)acryloyl groups per molecule. The (meth)acryloyl group-containing silane coupling agent refers to an organosilicon compound having at least a (meth)acryloyl group and a hydrolyzable group.
[0034] Examples of methods for forming an overcoat layer on a vapor deposition layer include a method of applying and drying a coating liquid for the overcoat layer that constitutes the overcoat layer, a method of adhering the overcoat layer with an adhesive, and a vapor deposition method such as flash vapor deposition.
[0035] The thickness of the overcoat layer is preferably 50 nm or more, more preferably 60 nm or more, from the viewpoint of protecting the deposition layer, and is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 350 nm or less, from the viewpoint of adhesion. As the barrier film layer, a commercially available barrier film may be used, for example, GL-AE and GL-AEY-W manufactured by Toppan Printing Co., Ltd., VA607 and VN508 manufactured by Toyobo Co., Ltd., and 1011HG-CR manufactured by Toray Advanced Film Co., Ltd.
[0036] <Heat seal layer> The paper laminate according to this embodiment has at least one heat seal layer on one side of the paper substrate, with a barrier film layer, a paper substrate layer, and a heat seal layer in this order. The heat seal layer is a layer that melts and adheres by heating, ultrasonic waves, etc. From the viewpoint of forming a heat seal layer on the paper substrate uniformly without defects, the paper laminate according to this embodiment preferably has two or more heat seal layers on one side of the paper substrate. In this case, the compositions of the two or more heat seal layers may be the same or different.
[0037] (Thickness) From the viewpoint of heat sealability and recyclability, for example, when the heat seal layer is formed by laminating using melt extrusion or adhesive, the thickness of the heat seal layer is preferably 5 μm or more, more preferably 10 μm or more, and preferably 70 μm or less, more preferably 60 μm or less. Also, for example, when the heat seal layer is formed by preparing a coating liquid for the heat seal layer and applying the coating liquid, the thickness is preferably 1 μm or more, more preferably 2 μm or more, even more preferably 3 μm or more, and preferably 30 μm or less, more preferably 20 μm or less. The thickness of the heat seal layer can be measured by taking an enlarged photograph of the vertical cross section of the paper laminate using a scanning electron microscope (for example, S-3600N, manufactured by Hitachi High-Tech Corporation).
[0038] The heat seal layer preferably contains at least one selected from the group consisting of polyolefin resins and water-dispersible resin binders. The water-dispersible resin binder is a resin binder that is not water-soluble but is finely dispersed in water, such as an emulsion or suspension. If the water-dispersible resin binder also falls under the category of a lubricant, it is classified as a lubricant.
[0039] (Polyolefin resin) Examples of polyolefin resins include polyethylenes (PE) such as very low density polyethylene (VLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), linear low density polyethylene, polypropylene (PP), ethylene / propylene copolymers, etc. Among these, polyethylene is preferred, and low density polyethylene is more preferred.
[0040] (Water-dispersible resin binder) The water-dispersible resin binder is, for example, preferably at least one selected from the group consisting of ethylene / vinyl acetate copolymers and olefin / unsaturated carboxylic acid copolymers, more preferably at least one selected from the group consisting of ethylene / vinyl acetate copolymers, ethylene / (meth)acrylic acid copolymers, and ethylene / (meth)acrylic acid alkyl ester copolymers, and even more preferably at least one selected from the group consisting of ethylene / vinyl acetate copolymers and ethylene / (meth)acrylic acid copolymers.
[0041] The ethylene / (meth)acrylic acid copolymer may be either a synthetic product or a commercially available product. Examples of commercially available products include MP498345N, MP4983R, and MP4990R manufactured by Michaelman Japan LLC, ZAIXXEN (registered trademark) A and ZAIXXEN (registered trademark) AC manufactured by Sumitomo Seika Chemicals Co., Ltd., and the Chemipearl S series manufactured by Mitsui Chemicals, Inc.
[0042] The content of the water-dispersible resin binder in the heat seal layer is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 45% by mass or more, and even more preferably 50% by mass or more, and is 100% by mass or less, preferably 90% by mass or less, and more preferably 80% by mass or less. Within the above ranges, a paper laminate having high heat seal strength can be obtained.
[0043] The heat seal layer may further contain other components in addition to the above resins, such as pigments, lubricants, and silane coupling agents.
[0044] [Physical properties of paper laminates] <Tensile energy absorption (TEA)> The paper laminate is designed to have a geometric mean of X1 and Y1 (the square root of the product of X1 and Y1) of 120 J / m2 or less, from the viewpoint of obtaining a paper laminate with excellent impact resistance and processability, where X1 is the tensile energy absorption in the longitudinal direction and Y1 is the tensile energy absorption in the transverse direction measured in accordance with JIS P 8113:2006, and Y1 is the tensile energy absorption in the transverse direction. 2 or more, preferably 160 J / m 2 More preferably, 200 J / m 2 More preferably, 230 J / m 2 More preferably, 250 J / m 2 From the viewpoint of processability, it is preferably 800 J / m 2 Less than or equal to 700 J / m 2 Less than 600 J / m, more preferably 600 J / m 2 Less than or equal to 550 J / m 2 The following is the result.
[0045] <Tensile Energy Absorption Specific (TEAI)> When the specific tensile energy absorption in the longitudinal direction of the paper laminate is X2 and the specific tensile energy absorption in the transverse direction is Y2, as measured in accordance with JIS P 8113:2006, the geometric mean of X2 and Y2 is 1.8 J / g or more, preferably 2.0 J / g or more, and more preferably 2.2 J / g or more, from the viewpoint of obtaining a paper laminate having excellent impact resistance and processability. The upper limit is not particularly limited, but is preferably 8.0 J / g or less, and more preferably 7.0 J / g or less.
[0046] <Basic weight> The basis weight of the paper laminate is preferably 80 g / m 2 More preferably, 100 g / m 2 More preferably, 105 g / m 2and preferably 200 g / m 2 Less than 180 g / m 2 More preferably, 170 g / m 2 The basis weight of the paper laminate is measured in accordance with JIS P 8124:2011.
[0047] <Thickness> From the viewpoint of impact resistance and processability of the paper laminate, the thickness of the paper laminate is preferably 100 μm or more, more preferably 120 μm or more, even more preferably 140 μm or more, and preferably 500 μm or less, more preferably 300 μm or less, even more preferably 250 μm or less. The thickness of the paper laminate is measured in accordance with JIS P 8118:2014.
[0048] <density> The density of the paper laminate is preferably 0.4 g / cm from the viewpoint of processability. 3 More preferably, 0.5 g / cm 3 More preferably, 0.6 g / cm 3 and preferably 1.5 g / cm 3 Less than or equal to 1.2 g / cm 3 More preferably, 1.0 g / cm 3 The density of the paper laminate is calculated from the basis weight and thickness of the paper laminate obtained by the above-mentioned measuring method.
[0049] <Tear strength> From the standpoint of impact resistance, the paper laminate preferably has a geometric mean of the tear strength in the longitudinal and transverse directions measured in accordance with JIS P 8116:2000 of 1000 mN or more, more preferably 1100 mN or more, and preferably 1900 mN or less, more preferably 1800 mN or less.
[0050] <Oxygen permeability> The paper laminate preferably has an oxygen transmission rate of 10 mL / m2 measured at 23°C and 50% RH. 2 ·atm·day or less, preferably 5.0mL / m 2·atm·day or less, more preferably 2.0mL / m 2 ·atm·day or less, even more preferably 1.0 mL / m 2 atm day or less, even more preferably 0.5 mL / m 2 ·atm·day or less. There is no particular lower limit for the oxygen permeability. The oxygen permeability of the paper laminate is measured by the method described in the Examples.
[0051] <Water vapor permeability> The paper laminate preferably has a water vapor transmission rate of 50 g / m2 measured at 40° C. and 90% RH. 2 ·day or less, preferably 30g / m 2 ·day or less, more preferably 10g / m 2 day or less, even more preferably 5.0 g / m 2 day or less, even more preferably 3.0 g / m 2 day or less, even more preferably 2.0 g / m 2 day or less, even more preferably 1.8 g / m 2 ·day or less. There is no particular lower limit for the water vapor permeability. The water vapor permeability of the paper laminate is measured by the method described in the Examples.
[0052] [Manufacturing method of paper laminate] The method for producing the paper laminate of this embodiment is not particularly limited. For example, a production method including a barrier film layer lamination step of laminating at least one barrier film layer on one side of a paper base obtained by a method including a cooking step of cooking raw pulp to have a kappa number of 30 to 60, a beating step of beating a dispersion containing 20% to 45% by mass of the cooked raw pulp, and a papermaking step of making paper from the beaten raw pulp, and a heat seal layer formation step of forming at least one heat seal layer by lamination or coating on the other side of the paper base can be used. Note that either the barrier film layer lamination step or the heat seal layer formation step can be performed first, and for example, when the heat seal layer formation step is performed twice or more, it can be performed in the order of a first heat seal layer formation step, a barrier film layer lamination step, and a second heat seal layer formation step, and is not particularly limited. Each step of the production method is described below.
[0053] <Manufacturing method of paper base material> (Cooking process) The cooking step is a step of cooking to make the kappa number of the raw pulp preferably 30 or more and 60 or less. Although not particularly limited, raw chips used as a material for the raw pulp are treated with a chemical solution containing sodium hydroxide to obtain raw pulp having a kappa number of 30 or more and 60 or less. As a treatment method with a chemical solution containing sodium hydroxide, a known treatment method using a known chemical solution can be used. By making the kappa number of the raw material pulp 30 or more and 60 or less, a paper base material and a paper laminate using the paper base material that satisfy the above TEA physical properties and TEAI physical properties and have impact resistance and processability can be obtained. From this viewpoint, the kappa number of the raw material pulp is preferably 50 or less, and more preferably 45 or less.
[0054] The raw material chips used as the material for the raw material pulp are preferably mainly composed of coniferous pulp. "Raw material chips mainly composed of coniferous pulp" refers to raw material chips having a coniferous content of more than 50% by mass, and the coniferous content is preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass.
[0055] The raw material pulp may be unbleached or may be bleached. The raw material pulp is preferably one or more selected from the group consisting of bleached kraft pulp and unbleached kraft pulp, and more preferably unbleached kraft pulp.
[0056] (beating process) The beating step is a step of beating a dispersion containing preferably 20% by mass or more and 45% by mass or less of the digested raw pulp. The method of beating is not particularly limited, but it is preferable to disperse the digested raw pulp in water to prepare a dispersion having the above-mentioned raw pulp concentration, and then beat the dispersion. The method of beating is not particularly limited, but it can be performed using a beater such as a double disc refiner, a single disc refiner, or a conical refiner. By beating a dispersion containing 20% by mass or more and 45% by mass or less of cooked raw pulp, a paper base material that satisfies the above-mentioned TEA properties and TEAI properties and has excellent impact resistance and processability, and a paper laminate using said paper base material can be obtained, which also has excellent productivity.
[0057] (Paper making process) The papermaking process is a process of making paper from beaten raw pulp. The papermaking method is not particularly limited, and examples thereof include an acidic papermaking method in which papermaking is performed at a pH of about 4.5, and a neutral papermaking method in which papermaking is performed at a pH of about 6 to about 9. In the papermaking process, chemicals for the papermaking process such as a pH adjuster, a defoamer, a pitch control agent, and a slime control agent can be appropriately added as necessary. The papermaking machine is also not particularly limited, and examples thereof include a continuous papermaking machine such as a fourdrinier type, a cylinder type, or a tilt type, or a multi-layer papermaking machine that combines these.
[0058] The paper base material used in the paper laminate of this embodiment can be obtained by a method including the above-mentioned cooking step, beating step, and papermaking step. After the papermaking step, a Clupak step of shrinking the paper web using Clupak equipment may be included as necessary. As the Clupak equipment, a known Clupak equipment can be used. The method for producing the paper base material used in the paper laminate of this embodiment is not limited to the above-mentioned method.
[0059] The method for producing the paper laminate of this embodiment may also include a surface treatment step in which the surface of the paper base material is treated with a chemical. Chemicals used in the surface treatment step include sizing agents, water-resistant agents, water retention agents, thickeners, lubricants, etc. Known devices can be used for the surface treatment step.
[0060] <Barrier film layer lamination process> The method for producing a paper laminate of this embodiment includes a barrier film layer lamination step of laminating a barrier film layer on one side of the paper base material obtained as described above, so as to have a barrier film layer, a paper base material layer, and a heat seal layer in this order. For example, the barrier film layer can be adhered and laminated on the paper base material using an adhesive or the like. A known adhesive can be used as the adhesive. Two or more barrier film layers may be laminated.
[0061] <Heat seal layer forming process> The manufacturing method of the paper laminate of this embodiment includes a heat seal layer formation step of forming a heat seal layer on one side of the paper base material obtained as described above so as to have a barrier film layer, a paper base material layer, and a heat seal layer in that order. Examples of methods for forming the heat seal layer include a method of laminating the heat seal layer using melt extrusion, an adhesive, etc., and a method of forming the heat seal layer by preparing a coating liquid for the heat seal layer and applying the coating liquid. A known adhesive can be used as the adhesive. Two or more heat seal layers may be formed.
[0062] When forming multiple heat seal layers on a paper substrate, the above-mentioned method of successively forming heat seal layers is preferred, but is not limited thereto, and a simultaneous multi-layer coating method may be adopted. The simultaneous multi-layer coating method is a method in which multiple types of coating liquids are discharged separately from a slit-shaped nozzle to form a liquid laminate, which is then coated on a paper substrate to simultaneously form multiple heat seal layers.
[0063] The solvent of the heat seal layer coating liquid is not particularly limited, and water or an organic solvent such as ethanol, isopropyl alcohol, methyl ethyl ketone, or toluene can be used. Among these, from the viewpoint of not causing the problem of volatile organic solvents, an aqueous solvent (preferably water) is preferred as the dispersion medium of the heat seal layer coating liquid. That is, the heat seal layer coating liquid is preferably an aqueous composition for heat seal layers. In addition, forming the heat seal layer by aqueous coating is advantageous for recyclability, and further reduction in environmental load due to reduction in the amount of plastic used can be expected. In this specification, "aqueous" means that the content of water in the solvent is 50% by mass or more, preferably 80% by mass or more. There are no particular limitations on the coating equipment used to apply the heat seal layer coating liquid to the paper substrate, and any known equipment may be used. The drying equipment for drying the heat seal layer is not particularly limited, and known equipment can be used.
[0064] The total coating amount of the heat seal layer (after drying) is preferably 1 to 50 g / m 2 and more preferably 2 to 30 g / m 2 and even more preferably 5 to 20 g / m 2 It is.
[0065] The paper laminate of this embodiment has excellent heat sealing properties, processability, and impact resistance, as well as excellent oxygen barrier properties and water vapor barrier properties, and can therefore be suitably used as packaging bags for food, household goods, daily necessities (soap, bath additives, powdered detergent, wet tissues), medical drugs, electronics, etc. EXAMPLES
[0066] Examples are given below to specifically explain the present invention, but the present invention is not limited to these examples. Unless otherwise specified, the following operations were performed under conditions of 23°C and 50% RH. Furthermore, in the examples and comparative examples, "parts" and "%" respectively refer to "parts by mass" and "% by mass" unless otherwise specified.
[0067] [Analysis and Evaluation] The paper laminates of the examples and comparative examples were subjected to the following analyses and evaluations.
[0068] <Tensile energy absorption amount, specific tensile energy absorption amount> The tensile energy absorption amount and the specific tensile energy absorption amount were measured in accordance with JIS P 8113:2006.
[0069] <Basic weight> The basis weight was measured in accordance with JIS P 8124:2011.
[0070] <Thickness> The thicknesses of the paper substrate and the barrier film layer were measured in accordance with JIS P 8118: 2014. The thickness of the heat seal layer was measured by taking an enlarged photograph of the vertical cross section of the paper laminate using a scanning electron microscope (S-3600N, manufactured by Hitachi High-Tech Corporation).
[0071] <Tear strength> The tear strength was measured in accordance with JIS P 8116:2000.
[0072] <Oxygen permeability> The oxygen permeability was measured using an oxygen permeability measuring device (OX-TRAN2 / 20, manufactured by MOCON) under conditions of 23° C. and 50% RH.
[0073] <Water vapor permeability> The water vapor permeability was measured in accordance with JIS Z 0208:1976 using a moisture permeability cup prepared so that the barrier film-laminated surface of the paper laminate was on the inside (Condition B: temperature 40±0.5°C, relative humidity 90±2%).
[0074] <Heat sealability> The resulting paper laminate was cut to a width of 2.5 cm and a length of 15 cm, and the front and back surfaces were cut to a length of 14.85 cm. 2 After overlapping the two pieces with an area of 100 mm, they were sealed for 2 seconds at a temperature of 150°C and a pressure of 0.2 MPa using a heat seal tester (manufactured by Tester Sangyo Co., Ltd.), cooled to room temperature, and peeled off by hand. The appearance of the two pieces was evaluated according to the following criteria. If the result was A, there was no problem in practical use. A: It is completely adhered and difficult to peel off by hand. B: At least some areas are not bonded. C: No adhesion at all
[0075] <Evaluation of pillow molding processability> The paper laminate was used to make pillow bags measuring 15 cm in length and 11 cm in width using a vertical pillow molding machine (Kawashima Seisakusho Co., Ltd., KBF6000X2), and the quality of the bags was evaluated according to the following criteria. A: It is possible to form pillow bags without any problems. B: It is a little difficult to mold, but it is possible to mold a pillow bag and there are no problems. C: The bag shape can be made, but there are defects such as wrinkles, deformation, and poor sealing. D: Impossible to make into a pillow bag shape
[0076] <Impact resistance evaluation> A paper laminate cut to 400mm length x 760mm width was folded in half with the heat-sealed layers facing each other to a size of 400mm length x 380mm width, and 3kg of gravel was placed inside and sealed with an impulse sealer (VG-400, manufactured by Fuji Impulse Co., Ltd.) with a seal width of 10mm to create five three-sided sealed bags. The three-sided sealed bags were dropped from a height of 60cm onto a concrete floor in the order of "1: bottom corner → 2: bottom → 3: side → 4: side → 5: top → 6: front side → 7: back side," and the state of damage to the bags was visually evaluated according to the following criteria. A: The above items 1 to 7 are considered as one set, and even if three sets are dropped, the bag will not be damaged (all five bags are in three sets and will not be damaged) B: The above 1 to 7 are considered as one set. The bag will not break within one set, but it may break within 2 to 3 sets (more than 1 out of 5 bags will break within 2 to 3 sets). C: The above 1 to 7 constitute one set, and the bag may break within one set (more than one bag out of five breaks within one set). D: The above items 1 to 7 constitute one set, and all five bags are damaged within one set.
[0077] Example 1 <Preparation of paper substrate> Using Douglas fir, a coniferous tree, as the raw material chips, a cooking treatment was performed using a chemical solution containing sodium hydroxide, and raw material pulp, which is unbleached kraft pulp with a kappa number of 45, was obtained. Next, the raw material pulp obtained by the cooking treatment was dispersed in water to prepare a 30% by mass dispersion. Thereafter, the dispersion was beaten using a single disc refiner and a double disc refiner as the beater to obtain kraft pulp. To the obtained kraft pulp, 0.2% by mass of a synthetic sizing agent (Sizepine MXE2, manufactured by Arakawa Chemical Industries Co., Ltd.), 1.0% by mass of aluminum sulfate, 0.8% by mass of polyacrylamide (DS744, manufactured by Seiko PMC Corporation), and 0.8% by mass of cationic starch (OPTIBOND3922, manufactured by Ingredion Japan Co., Ltd.) were added to obtain paper stock (paper base material) based on the bone dry mass of the kraft pulp. The obtained paper stock was made using a papermaking machine equipped with a Clupac system, and paper was made to a target basis weight of 100 g / m.2 A paper base material (ultra-stretch paper) was produced (the actual measured basis weight is shown in Table 1, and the same applies below). <Preparation of Paper Laminate> The stretched PET film surface of a barrier film (GL-AE, Toppan Printing Co., Ltd., thickness 12 μm) consisting of a stretched PET film, an aluminum oxide deposition layer, and an overcoat layer laminated in that order was attached to one side of the paper substrate using an adhesive (Polysol AX505ZH, Showa Denko K.K.). In addition, low-density polyethylene (L2340, Asahi Kasei Corporation) was melt-extruded onto the opposite side of the paper substrate and laminated to a thickness of 50 μm to form a heat seal layer, thereby producing a paper laminate. The analysis and evaluation results are shown in Table 1.
[0078] Example 2 The target paper base material is 80g / m 2 A paper laminate was obtained in the same manner as in Example 1, except that the paper was made using the above method.
[0079] Example 3 The raw pulp obtained by the cooking treatment in Example 1 was dispersed in a concentration of 3% by mass and beaten to prepare a paper base material with a target basis weight of 83 g / m. 2 A paper laminate was produced in the same manner as in Example 1, except that a paper base material (stretched paper cement) produced by papermaking in the above manner was used.
[0080] Example 4 The target paper base material is 78g / m 2 A paper laminate was produced in the same manner as in Example 3, except that the paper was made using the following method.
[0081] Example 5 Target basis weight for paper base material: 73g / m 2 A paper laminate was produced in the same manner as in Example 3, except that the paper was made using the following method.
[0082] Example 6 The paper base material obtained in the same manner as in Example 1 was spun into a fourdrinier continuous papermaking machine with a target basis weight of 84 g / m 2 A paper laminate was produced in the same manner as in Example 3, except that a paper base material (heavy-duty packaging paper) was produced by papermaking using the above-mentioned method.
[0083] Example 7 A paper laminate was prepared in the same manner as in Example 1, except that the PET film surface of a barrier film (VA607, manufactured by Toyobo Co., Ltd., thickness 12 μm) consisting of a PET film with aluminum oxide vapor-deposited on it and an overcoat layer laminated on top of that was bonded to one side of the paper substrate (ultra-stretch paper) prepared in Example 1 using an adhesive (Polysol AX505ZH, manufactured by Showa Denko K.K.).
[0084] Example 8 A paper laminate was prepared in the same manner as in Example 1, except that a PET film surface of a barrier film (VN508, manufactured by Toyobo Co., Ltd., thickness 15 μm) consisting of a nylon film with aluminum oxide vapor-deposited on it and an overcoat layer laminated on top of that was attached to one side of the paper base material prepared in Example 1 using an adhesive (Polysol AX505ZH, manufactured by Showa Denko K.K.).
[0085] Example 9 In Example 1, instead of laminating low-density polyethylene on the surface of the paper substrate opposite to the surface to which the gas barrier film was attached, an ethylene-methacrylic acid copolymer ionomer (Mitsui Chemicals, Inc., Chemipearl S-300) was coated in an amount (solid content) of 16 g / m 2 A paper laminate was produced in the same manner as in Example 1, except that the coating was performed so that the paper was coated in the following manner.
[0086] [Table 1]
[0087] Comparative Example 1 The target paper base material is 75g / m 2 A paper laminate was produced in the same manner as in Example 6, except that the paper was made using the following method. The analysis and evaluation results are shown in Table 2.
[0088] Comparative Example 2 The target paper base material is 78g / m 2 A paper laminate was produced in the same manner as in Example 6, except that the paper was made using the following method. The analysis and evaluation results are shown in Table 2.
[0089] Comparative Example 3 The base material was unbleached kraft paper (manufactured by Oji Materia Co., Ltd., basis weight 80 g / m 2 A paper laminate was produced in the same manner as in Example 1, except that ) was used. The analysis and evaluation results are shown in Table 2.
[0090] Comparative Example 4 The base material was unbleached kraft paper (manufactured by Oji Materia Co., Ltd., basis weight 100 g / m 2 A paper laminate was produced in the same manner as in Example 1, except that ) was used. The analysis and evaluation results are shown in Table 2.
[0091] Comparative Example 5 The base material was unbleached kraft paper (manufactured by Oji Materia Co., Ltd., basis weight 120 g / m 2 A paper laminate was produced in the same manner as in Example 1, except that ) was used. The analysis and evaluation results are shown in Table 2.
[0092] Comparative Example 6 The base material was unbleached kraft paper (manufactured by Oji Materia Co., Ltd., basis weight 130 g / m 2 A paper laminate was produced in the same manner as in Example 1, except that ) was used. The analysis and evaluation results are shown in Table 2.
[0093] [Table 2]
[0094] As can be seen from Table 1, the paper laminates of Examples 1 to 9 were excellent in pillow-shaped formability and impact resistance, whereas, as can be seen from Table 2, the paper laminates of Comparative Examples 1 to 6 were poor in pillow-shaped formability and impact resistance. [Industrial Applicability]
[0095] The paper laminate of the present invention has excellent heat sealing properties, processability and impact resistance, as well as excellent oxygen barrier properties and water vapor barrier properties, and can therefore be suitably used as packaging bags for food, household goods, daily necessities (soap, bath additives, powdered detergent, wet tissues), medical drugs, electronics, etc.
Claims
1. A paper laminate comprising a barrier film layer, a paper base layer, and a heat seal layer laminated in this order, the barrier film layer having a base film, a vapor deposition layer, and an overcoat layer in this order from the paper base side, the base film being made of a polymer selected from the group consisting of polyesters and polyamides, and the paper laminate having a longitudinal tensile energy absorption amount of X, as measured in accordance with JIS P 8113:2006. 1 The amount of tensile energy absorbed by the paper laminate in the lateral direction is Y 1 , the specific tensile energy absorption in the longitudinal direction of the paper laminate measured in accordance with JIS P 8113:2006 is expressed as X 2 The specific tensile energy absorption of the paper laminate in the lateral direction is Y 2 Then, X 1 and Y 1 The geometric mean is 250 J / m 2 or more, and X 2 and Y 2 The geometric mean of the paper laminate is 1.8 J / g or more.
2. The paper base material has a basis weight of 50 g / m 2 120g / m or more 2 2. The paper laminate of claim 1, wherein:
3. 3. The paper laminate according to claim 1, wherein the ratio of the basis weight of the paper substrate to the basis weight of the paper laminate is 0.5 or more.
4. 4. The paper laminate according to claim 1, wherein the geometric mean of the tear strength in the machine direction and the cross direction of the paper laminate, measured in accordance with JIS P 8116:2000, is 1000 mN or more.
5. The oxygen permeability of the paper laminate measured at 23°C and 50% RH is 10 mL / m 2 The paper laminate according to any one of claims 1 to 4, wherein the thermal expansion coefficient is 0.01 - atm - day or less.
6. The water vapor permeability of the paper laminate measured at 40°C and 90% RH is 50 g / m 2 The paper laminate according to any one of claims 1 to 5, wherein the average thermal expansion coefficient is 0.05 - 0.
15.
7. The basis weight of the paper laminate is 80 g / m 2 More than 200g / m 2 The paper laminate according to any one of claims 1 to 6, wherein:
8. The paper laminate according to any one of claims 1 to 7, wherein the barrier film layer has a thickness of 5 µm or more and 30 µm or less.
9. The paper laminate according to any one of claims 1 to 8, wherein the kappa number of the pulp constituting the paper base material is 30 or more and 60 or less.
10. The paper laminate according to any one of claims 1 to 9, wherein the heat seal layer has a thickness of 70 µm or less.
11. The paper laminate according to any one of claims 1 to 10, wherein the heat seal layer comprises at least one selected from the group consisting of polyolefin resins and water-dispersible resin binders.
12. A packaging bag comprising the paper laminate according to any one of claims 1 to 11.
Citation Information
Patent Citations
heavy duty paper bag
JP1995022944U
Laminate for packaging material
JP2003276131A
Paper bag
JP2005145561A
Newsprint paper for offset printing, which has less paper break on printing and method for predicting the paper break
JP2007247075A
Kraft paper
JP2014055372A